Recurrent selection shapes the genomic landscape of differentiation between a pair of host‐specialized haplodiploids that diverged with gene flow - Ashleigh N. Glover; Vitor C. Sousa; Ryan D. Ridenbaugh; Sheina B. Sim; Scott M. Geib; Catherine R. Linnen (Molecular Ecology, 2024)
Understanding the genetics of adaptation and speciation is critical for a complete picture of how biodiversity is generated and maintained. Heterogeneous genomic differentiation between diverging taxa is commonly documented, with genomic regions of high differentiation interpreted as resulting from differential gene flow, linked selection and reduced recombination rates. Disentangling the roles of each of these non‐exclusive processes in shaping genome‐wide patterns of divergence is challenging but will enhance our knowledge of the repeatability of genomic landscapes across taxa. Here, we combine whole‐genome resequencing and genome feature data to investigate the processes shaping the genomic landscape of differentiation for a sister‐species pair of haplodiploid pine sawflies, Neodiprion lecontei and Neodiprion pinetum . We find genome‐wide correlations between genome features and summary statistics are consistent with pervasive linked selection, with patterns of diversity and divergence more consistently predicted by exon density and recombination rate than the neutral mutation rate (approximated by dS). We also find that both global and local patterns of F ST , d XY and π provide strong support for recurrent selection as the primary selective process shaping variation across pine sawfly genomes, with some contribution from balancing selection and lineage‐specific linked selection. Because inheritance patterns for haplodiploid genomes are analogous to those of sex chromosomes, we hypothesize that haplodiploids may be especially prone to recurrent selection, even if gene flow occurred throughout divergence. Overall, our study helps fill an important taxonomic gap in the genomic landscape literature and contributes to our understanding of the processes that shape genome‐wide patterns of genetic variation.